Estudo do processo UV/H2O2 e da fotólise UVC na degradação do agrotóxico Lorsban® com acompanhamento da ecotoxicidade - Angeli, Suelen (2019)
Agrochemical waste is among the main stressors of aquatic ecosystems due to the indiscriminate use of these compounds, which represent a serious threat to biota, and also to human health, since most are toxic, mutagenic, teratogenic or carcinogenic. As a consequence of the recalcitrance of agrochemicals, several remediation technologies have been investigated. This work aimed to evaluate the degradation efficiency of Lorsban®, active chlorpyrifos (CP), UV/H2O2 process and UVC photolysis, together with bioassays to evaluate the ecotoxicity of solutions, pre and post treatment. The degradations were carried out in a 600 mL reactor using a high pressure mercury vapor lamp of 125 W, immersed in the solution and protected by a quartz bulb. In the degradation tests, the initial CP concentration was 200 μg L-1, and samples were generated at 30, 60, 90, 120, 240, 360 and 480 minutes for analysis by HPLC-DAD and ecotoxicity tests. Liquid-liquid extraction (ELL) was used for the chromatographic analyzes. The limit of quantification (LQ) of the chromatographic method was 0.06 μg L-1, and the limit of detection (LD) was 0.02 μg L-1. For the ecotoxicological tests three test organisms, Daphnia magna, Lactuca sativa seeds and Aedes aegypti larvae were used. After 60 minutes of treatment, CP was no longer observed (<LD), corresponding to a degradation higher than 99.99%. For the samples tested by D. magna, a reduction in the immobility of the organisms was observed only in 480 minutes by the UV/H2O2 process, whereas in the UVC photolysis 100% immobility was observed up to 90 minutes of treatment, with oscillation of the results from that time. For L. sativa seeds, the UV/H2O2 process showed inhibition of root growth at 60 and 240 minutes, while in the other samples the effect was not significant, and in UVC photolysis no significant effect was observed in any of the evaluated times. Regarding the tests with A. aegypti, at 60, 90, 120 and 480 minutes times, there was no immobility of the organisms in the UV/H2O2 process, and in the UVC photolysis no immobility was observed from 60 minutes onwards. Therefore, even reaching high CP degradation rates, in both processes, the bioassays demonstrated the importance of the analyzes of the effluent generated after the degradations, in order to make a deep and more conscious evaluation of the efficiency and viability of the treatments proposed.